Depression and cognitive impairment in institutionalized older adults. - Camacho-Conde, José Antonio (Karger, 2020)
Background: In the last three decades, the relationship between depression and cognition in geriatric patients has been a popular topic among researchers and clinicians. Clinical and epidemiological research has focused on the identification of risk factors that could be modified in pre-dementia syndromes, at a preclinical and early clinical stage of dementia disorders, with specific attention to the role of depression. The objective of this work was to determine the relationship between depressive disorder and cognitive deterioration in institutionalized older adults. Methods: In this descriptive, correlational study, data were gathered from two nursing homes in the province of Jaen (Spain), from a random sample of 140 older adults (70 nondependent and 70 dependent). The variables were measured using comprehensive geriatric assessment, the Cambridge Cognitive Test (CAMCOG), and the Geriatric Depression Scale (GDS). Results: Depression was correlated with cognitive level in the nondependent older adult sample (r = –0.471, p = 0.004). Age was inversely associated with the score obtained in the CAMCOG of the nondependent older adult sample (r = –0.352, p = 0.038). The functional capacity in several activities of daily living was correlated with the score obtained in the CAMCOG in each of the two groups. Depression was more prevalent in the dependent than in the nondependent older adults (82.85 vs. 57.14%). No association was observed between institutionalization time and the score obtained on the cognitive and affective scales (GDS and CAMCOG) in both groups (GDS-nondependent, r = –0.209, p = 0.234; CAMCOG-nondependent, r = 0.007, p = 0.967; GDS-dependent, r = 0.251, p = 0.152; CAMCOG-dependent, r = –0.021, p = 0.907). Conclusion: Depressive symptomatology is associated with cognitive deterioration. Depression is prevalent in institutions that care for older, more dependent adults
Política de acceso abierto tomada de: https://v2.sherpa.ac.uk/id/publication/8994
Keywords: Demencia; Depresión en ancianos; Depresión